2020
DOI: 10.1111/pbr.12872
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of gene‐based markers for shrunken2‐Reference allele and their utilization in marker‐assisted sweet corn (Zea maysSachharata) breeding programme

Abstract: The recessive shrunken2-Reference (sh2-Ref) allele is traditionally used in sweet corn cultivar development worldwide. However, non-availability of suitable gene-based marker(s) for sh2-Ref has considerably delayed its utilization in molecular breeding. Here, 7,320 bp sequence of Sh2 gene among five wild-and six sh2-Ref-based inbreds was analysed by employing 13 overlapping primers. SNP583 (A in wild and G in mutant) and SNP755 (T in wild and C in mutant) in 5'UTR, and SNP5112 (C in wild and T in mutant) in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Among these, six SNPs had a missense effect, two SNPs were located on the introns, and two SNPs were located upstream the first start codon ( Figure 4 ). These SNPs are different from those used to develop the gene-based markers for sh2-Reference allele [ 15 ]. The markers were designed on the basis of these 10 selected SNPs and validated in a set of 43 maize lines using a MassARRAY ® platform ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, six SNPs had a missense effect, two SNPs were located on the introns, and two SNPs were located upstream the first start codon ( Figure 4 ). These SNPs are different from those used to develop the gene-based markers for sh2-Reference allele [ 15 ]. The markers were designed on the basis of these 10 selected SNPs and validated in a set of 43 maize lines using a MassARRAY ® platform ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no report of functional markers associated with genes or QTLs underlying kernel sweetness in maize. Chhabra et al (2020) recently reported gene-based PCR markers that resided in the 5’UTR and intron-12 regions of the sh2 gene [ 15 ]. In this study, we extended the search for gene-based SNPs around our most associated SNP near the sh2 gene on chromosome 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US$ 1541.72 million and US$ 1475 million worth of import and export were recorded in sweet corn during 2020, respectively [ 7 ]. The kernel sweetness is genetically controlled, thus identification of mutations in gene(s) involved in the starch biosynthesis pathway provides gateway to enhance sweetness in kernels [ 8 , 9 ]. Amongst various mutations reported till date, a recessive shrunken2 ( sh2 ) gene located on chromosome 3L at bin location 3.09, has been widely used in the sweet corn breeding programmes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recessive sh2 mutation was first identified as loss of function gene [ 11 ] and it was later artificially selected by the breeders to develop sweet corn germplasm globally [ 12 , 13 ]. Using this sh2 mutant, large number of sh2 -based sweet corn inbreds and hybrids has been developed and commercialized [ 8 , 14 ]. Sh2 gene encodes the large subunit of ADP-glucose pyrophosphorylase ( AGPase ) that catalyzes the conversion of glucose-1-phosphate into ADP-glucose in the starch biosynthesis pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%